2022
DOI: 10.1155/2022/5141647
|View full text |Cite
|
Sign up to set email alerts
|

Simple Analytical Method on the Determination of Dexamethasone in Herbal Medicine

Abstract: Chemical drugs have been added to some of the traditional herbal medicine to enhance the therapeutic effect. One of them is dexamethasone which is added in herbal pain relief. To determine the content of dexamethasone in herbal medicine, a quantitative analytical method was developed with the reaction of the formation of a dexamethasone-hydroxylamine complex with fluoranil which was measured by UV-Vis spectrophotometry. Under optimized conditions, the performance of this system to analyze dexamethasone exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Then, they were stirred with a shaker at 90 rpm for 30 min. This solvent combination was used in previous studies to detect dexamethasone and showed good results, so the same combination was also used to extract dexamethasone in the herbal samples here [12]. The stirring process also served to ensure that the dexamethasone in the herbal samples could be optimally extracted.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, they were stirred with a shaker at 90 rpm for 30 min. This solvent combination was used in previous studies to detect dexamethasone and showed good results, so the same combination was also used to extract dexamethasone in the herbal samples here [12]. The stirring process also served to ensure that the dexamethasone in the herbal samples could be optimally extracted.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…These conditions indicated that there was a peak of dexamethasone at a retention time of 3.501 min with the UV detector at a wavelength of 240 nm, as shown in Figure S1. The conditions were optimized by fulfilling the parameters of the validation method, so the results of analyses using these conditions would show a proper detection of dexamethasone [12]. To be able to determine the level of dexamethasone in the sample, it was necessary to prepare a standard curve by using the dexamethasone standard in various concentrations.…”
Section: Accuracy Testmentioning
confidence: 99%
See 1 more Smart Citation